Effect of Galohgor Cookies and Powder Drinks on Visceral Adipose Tissue and Lipid Profile in Patients with Type 2 Diabetes Mellitus - Damayati, Ratih Putri; Roosita, Katrin; Sulaeman, Ahmad (Jurnal Gizi dan Pangan, 2018)
This study aimed to assess the intervention effect of cookies and galohgor powder drinks on visceral adipose tissue (VAT) and lipid profile in patients with type 2 diabetes mellitus. The study design was quasi experimental. Subjects of this study were 26 adults with type 2 diabetes mellitus in Bogor District, West Java. Subjects were divided into two intervention groups; cookies and galohgor powder drinks (GCPD) group and cookies and powder drinks without galohgor (CPD) group. Both interventions were given for 38 days period. Analysis of Covariance (ANCOVA) was applied to assess the effect of interventions. The average changes in VAT controlled by covariates in GCPD group was significantly higher than in CPD group (-33.3% vs +6.7%; p<0.05), while the average changes in blood total cholesterol  in GCPD group and CPD group were -8.5% and -3.8% (p>0.05). The average changes of triglycerides level in GCPD and with CPD group were -30.9% and +1.6% (p>0.05). The average changes in HDL level for GCPD group and CPD group were -9.0% and -12.0% (p>0.05). The average changes in LDL level for GCPD group and CPD group were -3.9% and -1.6% (p>0.05). Hence, it can be concluded that the administration of cookies and galohgor powder drinks significantly reduced the Visceral Adipose Tissue (VAT) in patients with type 2 diabetes mellitus.